Malaria as a public health problem and status of vaccine development - Abdullah, Wan Omar; Mohd Noh, Lokman (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2006)
Malaria remains one of the most important infectious diseases worldwide considering that 40% of the world’s population live in health risk areas and millions of febrile episodes due to malaria infection occur annually in children under the age of five in Africa alone and almost 3 million patients, primarily children, die each year. Among the various measures envisaged, to contain the disease, the concept of a vaccine to protect humans against malaria appears particularly attractive. The development of an effective malaria vaccine represents one of the most important approaches to provide cost-effective intervention, in addition to currently available malaria control strategies. Here, we review malaria as a public health problem and the status and promise in malaria vaccine development.